A novel compound heterozygous mutation of the CLCN7 gene is associated with autosomal recessive osteopetrosis - Wang, Xia; Wang, Yingcan; Xu, Ting; Fan, Yanjie; Ding, Yifeng; Qian, Jihong (Frontiers in Pediatrics, 2023)
Osteopetrosis is a genetic condition of the skeleton characterized by increased bone density caused by osteoclast formation and function defects. Osteopetrosis is inherited in the form of autosomal dominant and autosomal recessive manner. We report autosomal recessive osteopetrosis (ARO; OMIM 611490) in a Chinese case with a history of scarce leukocytosis, vision and hearing loss, frequent seizures, and severe intellectual and motor disability. Whole-exome sequencing (WES) followed by Sanger sequencing revealed novel compound heterozygous mutations in the chloride channel 7 (CLCN7) gene [c.982-1G > C and c.1208G > A (p. Arg403Gln)] in the affected individual, and subsequent familial segregation showed that each parent had transmitted a mutation. Our results confirmed that mutations in the CLCN7 gene caused ARO in a Chinese family. Additionally, our study expanded the clinical and allelic spectrum of the CLCN7 gene and enhanced the applications of WES technology in determining the etiology of prenatal diagnoses in fetuses with ultrasound anomalies.